Comparison of staged-stent and stent-assisted coiling technique for ruptured saccular wide-necked intracranial aneurysms: Safety and efficacy based on a propensity score-matched cohort study - Zhang, Guanghao; Zhang, Renkun; Wei, Yanpeng; Chen, Rundong; Zhang, Xiaoxi; Xue, Gaici; Lv, Nan; Duan, Guoli; Wang, Chuanchuan; Yu, Ying; Dai, Dongwei; Zhao, Rui; et al. (Frontiers in Neurology, 2023)
Background: Application of stent-assisted coiling and FD in acute phase of ruptured wide-necked aneurysms is relatively contraindicated due to the potential risk of ischemic and hemorrhagic complications. Scheduled stenting after initial coiling has emerged as an alternative paradigm for ruptured wide-necked aneurysms. The objective of this study is to evaluate the safety and efficacy of a strategy of staged stent-assisted coiling in acutely ruptured saccular wide-necked intracranial aneurysms compared with conventional early stent-assisted coiling strategy via propensity score matching in a high-volume center. Methods: A retrospective review of patients with acutely ruptured saccular wide-necked intracranial aneurysms who underwent staged stent-assisted coiling or conventional stent-assisted coiling from November 2014 to November 2019 was performed. Perioperative procedure-related complications and clinical and angiographic follow-up outcomes were compared. Results: A total of 69 patients with staged stent-assisted coiling and 138 patients with conventional stent-assisted coiling were enrolled after 1:2 propensity score matching. The median interval time between previous coiling and later stenting was 4.0 weeks (range 3.5-7.5 weeks). No rebleeding occurred during the intervals. The rate of immediate complete occlusion was lower with initial coiling before scheduled stenting than with conventional stent-assisted coiling (21.7% vs 60.9%), whereas comparable results were observed at follow-up (82.5% vs 72.9%; p = 0.357). The clinical follow-up outcomes, overall procedure-related complications and procedure-related mortality between the 2 groups demonstrated no significant differences (P = 0.232, P = 0.089, P = 0.537, respectively). Multivariate analysis showed that modified Fisher grades (OR = 2.120, P = 0.041) were independent predictors for overall procedure-related complications and no significant predictors for hemorrhagic and ischemic complications. Conclusions: Staged stent-assisted coiling is a safe and effective treatment strategy for acutely ruptured saccular wide-necked intracranial aneurysms, with comparable complete occlusion rates, recurrence rates at follow-up and overall procedure-related complication rates compared with conventional stent-assisted coiling strategy. Staged stent-assisted coiling could be an alternative treatment option for selected ruptured intracranial aneurysms in the future.